Gambaran Hemodinamik Intra Anestesi dan Retensi Urin Pasca Operasi Pada Pasien Sectio Caesarea Dengan Metode Enhanced Recovery After Caesarean Section (ERACS) di RSIA Permata Hati Mataram - Faristanty, Audria Noviand; Susanto, Amin; Suandika, Made (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The birth of a fetus through an incision in the uterine wall through the front wall of the abdomen is known as sectio cesarean delivery. The SC process requires anaesthetic management consisting of general and regional anaesthesia. Female celebrities and general citizens are currently having SC deliveries using the Enhanced Recovery After Cesarean Surgery (ERACS) method. Spinal anaesthesia provides several advantages, including keeping the mother awake, reducing aspiration likelihood, and avoiding neonatal depression. It also provides unexpected complications, including haemodynamic changes and the incidence of urinary retention. This study aims to determine the features of intra-anesthetic haemodynamics and postoperative urinary retention in sectio caesarea patients with the Enhanced Recovery After Cesarean Surgery (ERACS) method. This study used a quantitative descriptive approach with a cross-sectional approach. The sampling technique was a purposive sampling of as many as 67 respondents. Data were collected by observing the first 15 minutes after spinal anaesthesia and interviewing the incidence of postoperative urinary retention. The results showed that there were haemodynamic changes and the incidence of postoperative urinary retention.